1984
DOI: 10.1111/j.1399-3054.1984.tb06350.x
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous auxin levels in terminal stem cuttings of Chrysanthemum morifolium during adventitious rooting

Abstract: Weigel, U., Horn, W. and Hock, B. 1984. Endogenous auxin levels in stem cuttings of Chrysatuhemum tnorifoUum during adventitious rooting. -Physiol. Plant 61 • 422-428.Free and ester-bound IAA were determined in Chtysattthemum tnorifoliutn Ratnat cv. 'Yellow Galaxy' by means of a solid phase enzyme immunoassay. In shoots, free auxin decteases basipetally whereas ester IAA teaches a maximum in the middle part. After making the cuttings, a strong increase in both free and ester iAA (or total IAA, respectively) is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
22
0
1

Year Published

1986
1986
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 29 publications
6
22
0
1
Order By: Relevance
“…This was also supported by [12] who found that carbohydrate aids in auxin transport as well as growth of the roots and increased number of roots per cutting. [13] also speculated that mobilization of carbohydrate in the leaves and upper stem to the rooting zone is influenced by hormone application.…”
Section: Comparison Between Soluble Insoluble Total Sugars and Totasupporting
confidence: 69%
“…This was also supported by [12] who found that carbohydrate aids in auxin transport as well as growth of the roots and increased number of roots per cutting. [13] also speculated that mobilization of carbohydrate in the leaves and upper stem to the rooting zone is influenced by hormone application.…”
Section: Comparison Between Soluble Insoluble Total Sugars and Totasupporting
confidence: 69%
“…Chrysanthemum morifolium shoot tip LAA levels ranged from 15.6 to 29.0 ng/g FW, which is also considerably lower than E. esula root bud-free LAA levels. On the other hand, E. esula primary root-free IAA levels were very similar to levels of free IAA reported for primary root tissue of Zea mays (21), vegetative tissue of Z. mays, Pisum sativum (1,2), and Avena sativa (2), and also similar to free IAA levels in stem cuttings of C. morifolium (25).…”
Section: Discussionsupporting
confidence: 51%
“…Kawaoka et al (2010) observaram que clones de Eucalyptus globulus que apresentaram maiores taxas de enraizamento (90 %) em sistema de micropropagação tinham três vezes mais ácido indol-3-acético (AIA) endógeno do que clones com baixo enraizamento (10 %). Aumento no conteúdo de AIA também foi observado em estacas de Chrysanthemum morifolium (WEIGEL et al, 1984) e de videira (GASPAR et al, 1992) logo após a coleta das estacas nas plantas matrizes. No entanto, mais estudos deveriam ser implementados com Eucalyptus, relacionando o enraizamento de estacas com a expressão de auxinas endógenas e também com o balanço interno de fitorreguladores, como a relação auxina/citocinina.…”
Section: Figure 3 -Rooting (Ecs -A) and Number Of Roots Per Mini-cuttunclassified